2015
DOI: 10.1080/13540602.2015.1058592
|View full text |Cite
|
Sign up to set email alerts
|

Tensions between knowledge transmission and student-focused teaching approaches to assessment purposes: helping students improve through transmission

Abstract: This study surveyed 1,064 Chinese school teachers' approaches to teaching and conceptions of assessment, and examined their inter-relationship using confirmatory factor analysis and structural equation modeling. Three approaches to teaching (i.e., Knowledge Transmission, Student-Focused, and Examination Preparation) and six conceptions of assessment (i.e., Student Development, Teaching Improvement, Examination, Control, School Accountability, and Irrelevance) were identified. Teachers indicated they used Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…It is claimed that the three approaches are qualitatively distributed along a teacher‐oriented and student‐oriented continuum. The evidence has proved that it is possible for teachers to embrace multiple and even conflicting approaches to teaching (Chen & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is claimed that the three approaches are qualitatively distributed along a teacher‐oriented and student‐oriented continuum. The evidence has proved that it is possible for teachers to embrace multiple and even conflicting approaches to teaching (Chen & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students from CHC, as rote learners, always are taught to learn concepts or take tests through memorization (Tran, ). At the same time, there is a strong Confucian views that teachers should fully commit to students and the teaching profession and the student‐oriented teaching approach as a means to develop students into lifelong learners (Chen & Brown, ). These conflicting conceptions about what constitutes excellent teaching is well established in CHC (Watkins & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies focused on all kinds of subjects and mainly in secondary education (e.g., Brown & Gao, 2015;Chen & Brown, 2016). To our knowledge, only scarce attention has been paid in research to whether, and to what extent, the new approach to assessment has been implemented in primary mathematics classroom.…”
Section: Implementation Of the Assessment Reform In Primary School Mamentioning
confidence: 99%
“…in Australia: Brown, Lake, & Matters, 2011;in New Zealand: Brown, 2004;in India: Brown, Chaudhry, & Dhamija, 2015;in China: Brown, Kennedy, Fok, Chan, & Yu, 2009;Chen & Brown, 2016) revealed that teachers in general, mathematics teachers included, tend to embrace the idea of using assessment to improve teachers' instruction and students' learning by the provision of quality information for making instructional decisions. Furthermore, a later study carried out in New Zealand by Brown (2009) showed that having improvement-orientated assessment beliefs can predict teachers' increased assessment practice.…”
Section: Literature Review Teachers' Assessment Practice and Beliefsmentioning
confidence: 99%
“…Teacher-centred approaches may result whereby the teacher predominantly controls what is taught, and transmits knowledge, skills and values to students. This approach emphasises organising and presenting the course content in a way that is easy for students to understand in order to optimise their chances of achieving the learning outcomes (Chen & Brown, 2016).…”
Section: How Curriculum Policy Shapes Pedagogiesmentioning
confidence: 99%